Cross-conjugated BODIPY pigment for highly efficient dye sensitized solar cells. Issue 4 (4th February 2020) - Shah, Md Faiz; Mirloup, Antoine; Chowdhury, Towhid H.; Sutter, Alexandra; Hanbazazah, Abdulkader S.; Ahmed, Anas; Lee, Jae-Joon; Abdel-Shakour, M.; Leclerc, Nicolas; Kaneko, Ryuji; Islam, Ashraful
Abstract : In this study, we report a new BODIPY-based design, called the cross-conjugated design, that takes advantage of the α- and β-position functionalization of the BODIPY core. Abstract : In this study, we report a new BODIPY-based design, called the cross-conjugated design, that takes advantage of the α- and β-position functionalization of the BODIPY core. After synthesis, and compared to a more standard BODIPY dye, using similar functional groups and based on a horizontal design, called h -BOD, the new cross-conjugated BODIPY dye ( cc -BOD ) exhibits clearly the highest conjugation and light harvesting properties. Consequently, when used as photosensitizers in dye-sensitized solar cells (DSSCs), an impressive improvement of power conversion efficiency (PCE) has been observed, with a PCE of 6.02% with broad incident photon to current conversion efficiency (IPCE) for cc -BOD, compared to only 3.7% for h -BOD . Moreover, by co-sensitizing a DSSC with the two complementary absorbing dyes h -BOD and cc -BOD, we further improved the PCE up to 6.2%.